Blitzscaling: Doing organizational hypergrowth. - Coelho, J. V. (Weekonomics, 2019)
Blitzscaling is what can be called both the general framework and the specific techniques that allow companies to achieve massive scale at fast-paced speed. Amazon’s growth in the late 1990s (and up through today) is a prime example of blitzscaling. Classic approaches to business strategy involves gathering information and making decisions when one is confident of the results. Efficiency and certainty, while innately appealing, and very important in the context of a stable, established markets, offer little guidance to the disruptors, inventors, and innovators of the world. When a market is up for grabs, the risk isn’t inefficiency — the risk is playing it too safe.